2020
DOI: 10.1097/prs.0000000000007378
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Correlation between Altmetric Score and Citations in the Plastic Surgery Literature

Abstract: Background: Social media are transforming the dissemination of published research. This influence brought the advent of a new metric, altmetrics, which seeks to quantify the influence of research in real time based on an article’s attention online. This study aims to determine the correlation between altmetrics ratings for articles with traditional bibliometrics of impact factor and citation rate. Methods: The 10 most cited articles in the top 15 plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 7 publications
2
36
0
Order By: Relevance
“…The digitization and Open Access movement positively influence the immediacy effect of social media activities [25,26]. In fact, social media posts with Digital Object Identifiers (DOI) and links to public archiving sites such as PubMed Central attract societal attention to scholarly articles and increase citations across medical and allied health disciplines [27,28].…”
Section: Complementary Use Of Altmetric Analysesmentioning
confidence: 99%
“…The digitization and Open Access movement positively influence the immediacy effect of social media activities [25,26]. In fact, social media posts with Digital Object Identifiers (DOI) and links to public archiving sites such as PubMed Central attract societal attention to scholarly articles and increase citations across medical and allied health disciplines [27,28].…”
Section: Complementary Use Of Altmetric Analysesmentioning
confidence: 99%
“…Researchers have previously examined the dissemination of research in various plastic surgery publications using Altmetric Attention Scores (AAS). 4,5 For instance, Boyd et al compared Altmetric scores with traditional bibliometrics for the 10 most cited articles in the top plastic surgery journals and found the two variables were not strongly correlated. 4 Additionally, Asaad et al examined AAS and citation counts of the top six plastic surgery journals in 2016, and found that Plastic and Reconstructive Surgery (PRS) was the journal with the Disclosure: Dr. Kevin C. Chung receives funding from the National Institutes of Health, book royalties from Wolters Kluwer and Elsevier, and is a consultant for Axogen and Integra.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 For instance, Boyd et al compared Altmetric scores with traditional bibliometrics for the 10 most cited articles in the top plastic surgery journals and found the two variables were not strongly correlated. 4 Additionally, Asaad et al examined AAS and citation counts of the top six plastic surgery journals in 2016, and found that Plastic and Reconstructive Surgery (PRS ) was the journal with the second highest mean AAS after the Aesthetic Surgery Journal. 5 Nonetheless, there is a lack of research examining difference in the dissemination of a traditional plastic surgery journal with an OA counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…Using the Journal Citation Reports , 15 plastic surgery journals with the highest impact factor in 2019 were selected and all articles published in these journals in 2020 were extracted. 2 For the 6815 articles identified, number of citations accrued and Altmetric score, which is a weighted calculation of the attention an article receives online, were recorded. 3 COVID-19–related articles were identified by searching titles for “COVID,” “SARS,” “pandemic,” “corona,” “COVID-19,” or “SARS-CoV-2,” resulting in a total of 220 articles (3.2 percent).…”
mentioning
confidence: 99%